2014
DOI: 10.12968/bjcn.2014.19.sup4.s20
|View full text |Cite
|
Sign up to set email alerts
|

Redefining essential care in lymphoedema

Abstract: The awareness, diagnosis and management of chronic oedema and lymphoedema is improving. The enduring treatment format for the condition has always been regarded as the 'four cornerstones' of care for maintenance therapy in the UK. However, with changes in technology, availability of additional treatments and increased research and studies, this baseline is changing. This article outlines some of the recent changes and advancement in diagnostic tools and new technologies used in diagnosing and managing lymphoed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 10 publications
0
27
0
2
Order By: Relevance
“…15 A more substantial series of descriptive papers has discussed the FarrowWrap system for lymphoedema, originally brought to the UK market by Haddenham Healthcare. 11,[16][17][18][19] FarrowWrap is an adjustable hook and loop fastener system with multiple overlapping neoprene bands, interconnected by a spine. A case study described its' use in a young women with low mood who was not keen to have intensive bandaging treatment.…”
Section: Adjustable Compression Wrap Devices In People With Chronic Omentioning
confidence: 99%
See 2 more Smart Citations
“…15 A more substantial series of descriptive papers has discussed the FarrowWrap system for lymphoedema, originally brought to the UK market by Haddenham Healthcare. 11,[16][17][18][19] FarrowWrap is an adjustable hook and loop fastener system with multiple overlapping neoprene bands, interconnected by a spine. A case study described its' use in a young women with low mood who was not keen to have intensive bandaging treatment.…”
Section: Adjustable Compression Wrap Devices In People With Chronic Omentioning
confidence: 99%
“…16 Hobday and Wigg 19 describe the product as encouraging practitioners to take a creative, problem-solving approach to care, working in partnership with the patient. Both devices are reported as versatile and easily adjusted to a change in limb size to enable self-management of oedema reduction 10,18 , while also allowing for skin care to be carried out on a regular basis. 19 FarrowWrap has also been suggested as a useful garment for night use and compared favourably to short stretch bandaging 20 , although research evidence is lacking and the above papers are all descriptive in nature with only two research studies identified.…”
Section: Adjustable Compression Wrap Devices In People With Chronic Omentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it can be debated whether the tools used in advanced assessment are actually advanced or essential in obtaining a diagnosis for the patient. It is often easy to diagnose a patient with a dependency oedema from the clinical questioning and physical examination, but it is much more diffi cult to draw a conclusion of diagnosis when the patient has a type of primary lymphoedema or questioning leads to other causes [22].…”
Section: Clinical Evaluation and Diagnosismentioning
confidence: 99%
“…This reduces the requirement for regular dressing changes; however, it does not replace the necessity of daily washing and moisturising of the skin. This situation is particularly important where there are high levels of dryness, skin sensitivity or hyperkeratosis [22].…”
Section: Skin Carementioning
confidence: 99%